Adverse childhood experiences are associated with perceived cognitive difficulties among high school students in the United States - Ila A. Iverson; Nathan E. Cook; Nathan E. Cook; Nathan E. Cook; Grant L. Iverson; Grant L. Iverson; Grant L. Iverson; Grant L. Iverson (Frontiers in Psychology, 2024)
ObjectiveAdverse childhood experiences (ACEs) are associated with mental health and cognitive problems, and mental health problems are associated with perceived cognitive difficulties among adolescents. The unique contribution of ACEs to cognitive difficulties after adjusting for poor mental health is not well understood and represents the purpose of this study.MethodsThe Adolescent Behaviors and Experiences Survey was conducted in 2021 with high school students in the United States. Cognitive difficulty was assessed with: ‘Because of a physical, mental, or emotional problem, do you have serious difficulty concentrating, remembering, or making decisions?’ Four ACEs were examined: sexual violence (lifetime and past 12 months), parental emotional abuse, and parental physical abuse. Students were asked about feeling sad or hopeless (past year), considering suicide (past year), and having poor mental health (past month). Binary logistic regressions examined the association between ACEs and cognitive problems, adjusting for mental health.ResultsParticipants were 6,945 students. Students reporting poor mental health were very likely to endorse difficulty concentrating, remembering, or making decisions (girls = 81% and boys = 67%). Cognitive difficulty was uncommon among students who denied poor mental health (girls = 17% and boys = 12%). For boys [p < 0.001; R2 = 0.22] and girls [p < 0.001; R2 = 0.31], after adjusting for mental health problems, independent predictors of cognitive difficulties included parental verbal abuse and physical abuse. For girls, lifetime forced sexual intercourse and sexual violence during the past year were also independently associated.ConclusionACEs are associated with perceived cognitive difficulty in both adolescent girls and boys, even after adjusting for poor mental health.